Pengaruh Flash Sale dan Limited-Time Offers terhadap Impulsive buying behavior pada Pengguna Shopee - Mukhammad Nadhif Fuad; Syarif Hidayatullah; Alvin Dwi Yunianto; Edita Rachma Kamila (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
The development of e-commerce has driven changes in consumer behavior, particularly in the form of impulsive buying triggered by various digital promotional strategies. This study aims to analyze the effect of Flash Sales and Limited-Time Offers on impulsive buying behavior among Shopee users. The research method used is a qualitative approach with a literature study design through a targeted literature review. Data were obtained from various relevant national and international journal articles published between 2020 and 2025. The results of the study show that Flash Sales and Limited-Time Offers have a significant influence on increasing consumers' tendency to make impulsive purchases. Time pressure, perceived scarcity, and emotional urges such as Fear of Missing Out (FOMO) are the main factors that influence spontaneous purchasing decisions. Flash Sales tend to have a more direct impact through large discounts and short durations, while Limited-Time Offers work by creating a perception of exclusive value. This research contributes theoretically to the development of digital consumer behavior studies and provides practical implications for e-commerce players in designing effective and sustainable time-based promotional strategies.